Coronary artery disease in patients with severe aortic stenosis - Jáuregui, Marcos (2011)
Backgroud: Severe aortic stenosis (SOS) shares risk factors with coronary artery disease (CAD); however its prevalence has not been determined with precision. Objectives: To determine the prevalence of coronary artery disease in patients with severe aortic stenosis, risk factors, and the association between severe aortic stenosis classical symptoms and the presence of coronary artery disease. Design: Cross sectional quantitative observational study. Setting: Cardiology Department, Hospital Nacional Edgardo Rebagliati Martins, EsSalud, Lima, Peru. Participants: Patients with diagnosis of SOS who were catheterized. Interventions: We reviewed clinical charts and angiograms of 92 patients with diagnosis of SOS catheterized between January 2006 and December 2008, determining risk factors for CAD, symptoms and maximal aortic gradient; by using angiography we quantified the number of arteries with significant lesions as well as CAD severity by Gensini’s score in a randomized sample of 40 patients. Main outcome measures: CAD risk factors and correlation between CAD severity and maximal aortic gradient. Results: Age of the 92 patients averaged 69,8 years; 68,5% presented at least one risk factor for CAD with 16,3% prevalence. The only factor determining CAD in SOS patients was age (adjusted OR = 1,19; p=0,04). No classical SOS symptom was associated with CAD (p>0,05). There was no correlation between CAD severity –as determined by Gensini’s score- and maximal aortic gradient. Conclusions: Prevalence of coronary artery disease was16%; the only one factor associated to coronary artery disease was age and there was no association between any symptom and coronary artery disease.